Ultra‐Steep Slope Impact Ionization Transistors Based on Graphene/InAs Heterostructures. Issue 1 (29th September 2020) - Liu, Yuan; Guo, Jian; Song, Wenjing; Wang, Peiqi; Gambin, Vincent; Huang, Yu; Duan, Xiangfeng
Abstract : With the continued scaling of transistors, there is a growing trend for developing steep slope transistors with subthreshold swing (SS) below Boltzmann limitation ( k T/ q ). To this end, impact ionization metal oxide semiconductor (I‐MOS) transistors are attractive for a unique combination of high ON‐state current density, small hysteresis, and ultra‐steep SS slope. However, the performance of I‐MOS is generally limited by the relatively thick depletion region and large operation voltage required for the activation of impact ionization (typically >5 V). Herein, a high‐performance I‐MOS is constructed by van der Waals integrating single‐crystal InAs film with graphene. Due to the low bandgap of InAs as well as the semi‐metallic nature of graphene, the InAs/graphene I‐MOS demonstrates a low operation voltage of 1.5 V, high ON‐state current of 230 μA μm −1, steep SS <0.6 mV dec −1, and large ON–OFF ratio >10 6 at temperature below 200 K. Furthermore, a negative transconductance and steep current oscillation is observed in the subthreshold regime, and a device working mechanism is proposed for this novel phenomenon. This study not only pushes the performance limit of I‐MOS but also defines a general pathway to van der Waals heterostructures between conventional III–V compound semiconductors and novel 2D materials for unconventional device functions. Abstract : Herein, the authors construct impact ionization transistors by van der Waals integrating single‐crystal InAs film with graphene. Due to the low bandgap of InAs as well as the semi‐metallic nature of graphene, the heterostructure device demonstrates low operation voltage of 1.5 V as well as ultra‐steep subthreshold swing <0.6 mV dec −1 at low temperature.